Mechanism and Regulation of Silique Dehiscence, Which Affects Oil Seed Production - Yu, Yan-Kun; Li, Yu-Long; Ding, Li-Na; Sarwar, Rehman; Zhao, Feng-Yun; Tan, Xiao-Li (Frontiers in Plant Science, 2020)
Silique dehiscence is an important physiological process during natural growth that enables mature seeds to be released from plants, which then undergo reproduction and ensure the survival of future generations. In agricultural production, the time and degree of silique dehiscence affect the harvest time and processing of crops. Premature silique dehiscence leads to seeds being shed before harvest, resulting in substantial reductions to yields. Conversely, late silique dehiscence is not conducive to harvesting, and grain weight and oil content will be reduced due to the respiratory needs of seeds. In this paper, the mechanisms and regulation of silique dehiscence, and its application in agricultural production is reviewed.